The extent of aortic annulus calcification is a predictor of postprocedural eccentricity and paravalvular regurgitation: a pre- and postinterventional cardiac computed tomography angiography study - Bekeredjian, Raffi; Bodingbauer, Dorothea; Hofmann, Nina; Greiner, Sebastian; Schütz, Moritz; Geis, Nicolas; Kauczor, Hans-Ulrich; Bryant, Mark; Chorianopoulos, Emmanuel; Pleger, Sven Torsten; Mereles, Derliz; Katus, Hugo; et al. (The journal of invasive cardiology, 2015)
To investigate if the extent of aortic valve calcification is associated with postprocedural prosthesis eccentricity and paravalvular regurgitation (PAR) in patients undergoing transcatheter aortic valve implantation (TAVI). - Cardiac computed tomography angiography (CCTA) was performed before and 3 months after TAVI in 46 patients who received the self-expanding CoreValve and in 22 patients who underwent balloon-expandable Edwards Sapien XT implantation. Aortic annulus calcification was measured with CCTA prior to TAVI and prosthesis eccentricity was assessed with post-TAVI CCTA. Standard echocardiography was also performed in all patients at 3-month follow-up exam. - Annulus eccentricity was reduced during TAVI using both implantation systems (from 0.23 ± 0.06 to 0.18 ± 0.07 using CoreValve and from 0.20 ± 0.07 to 0.05 ± 0.03 using Edwards Sapien XT; P<.001 for both). With Edwards Sapien XT, eccentricity reduction at the level of the aortic annulus was significantly higher compared with CoreValve (P<.001). Annulus eccentricity after CoreValve use was significantly related to absolute valve calcification and to valve calcification indexed to body surface area (BSA) (r = 0.48 and 0.50, respectively; P<.001 for both). Furthermore, a significant association was observed between aortic valve calcification and PAR (P<.01 by ANOVA) in patients who received CoreValve. Using ROC analysis, a cut-off value over 913 mm² aortic valve calcification predicted the occurrence of moderate or severe PAR with a sensitivity of 92% and a specificity of 63% (area under the curve = 0.75). Furthermore, multivariable analysis showed that aortic valve calcification was a robust predictor of postprocedural eccentricity and PAR, independent of the aortic annulus size and native valve eccentricity and of CoreValve prosthesis size (adjusted r = 0.46 and 0.50, respectively; P<.01 for both). Such associations were not present with the Edwards Sapien XT system. - The extent of native aortic annulus calcification is predictive for postprocedural prosthesis eccentricity and PAR, which is an important marker for long-term mortality in patients undergoing TAVI. This observation applies for the CoreValve, but not for the Edwards Sapien XT valve.
Gesehen am 29.05.2020